Light Requirements of Shorea Materialis Seedlings - Mohamad, Aminuddin (1986)
This paper deals with the growth responses of Shorea materialis seedlings to various light conditions under shade chambers of21 %, 33% a1}-d 55% Relative Light Intensities (RLI), compared to open conditions (100% RLI). The best growth was observed between 30 - 55% RLI in terms of optimum increases in height, stem diameter, leaf area and overall dry matter. The weight ratio of shoot to root in the open is lower than that in the shade conditions.